Sistem Pendidikan Nasional di Pondok Pesantren - Nurresa Fi Sabil Resya; Fery Diantoro (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
Many teenagers do not continue school or drop out of school because of a lack of awareness of the importance of education, even though in the national education system one of the latest educational programs in the country is "Compulsory Learning for 12 Years", namely 6 years of Elementary School (SD), 3 years of Junior High School (SMP), and High School (SMA). This article tries to explain the importance of national education in facing the challenges of globalization and preparing the competitiveness of a nation that fears God Almighty. The method used is library research (library research). The theory used is descriptive analysis. The results of the study show that national education based on Pancasila, aims to increase devotion to God Almighty, intelligence and skills, enhance character, strengthen personality, and strengthen the spirit of nationalism and love for the homeland, in order to grow development humans who can build themselves. and jointly responsible for the development of the nation. Islamic boarding schools are genuine Indonesia. National education should be oriented towards pesantren education by inculcating open and tolerant human relations. Whereas the content of Article 3 of the National Education System Law is to develop capabilities and shape character and Islamic boarding schools have been implementing them for a long time. Through the Islamic boarding school which is a traditional educational institution that forms independence, discipline, responsibility, and moral reference as well as forming character education which is the basic capital in Islamic life in society and the state and achieves a complete human being to the students.